Mapping the use of planning support in a strategy-making session - Champlin, Carissa; Hartmann, Timo; Dewulf, Geert P. M. R. (AESOP, 2018)
This paper introduces an alternative means of evaluating the performance of planning support systems. These systems that were originally developed to support the professional tasks of planners have been assessed primarily based on their task-technology-user fit. During the tasks of early planning phases, planning actors attempt to adapt planning issues out of their ‘wicked’ state and into clear directions for action by means of communication. The search for better support of adaptations that result from these complex, multi-actor communications requires a more dynamic means of evaluating planning support. To gain a deeper understanding of planning support use during actor communications, we conducted a strategy-making session using preliminary modelling, sketching, facilitation and traditional support tools. We visualized the session as a network of communicative interactions and identified planning support involvement during key issue adaptations. Findings show that preliminary modelling and sketching were often used when identifying planning issues and adapting them into attributes for scenario development and that unsupported dialogue was used to communicate in depth about project objectives. We conclude that introducing planning support as needed in formats that are both visual and easy-to-understand may add value to strategy making in workshop settings.
plaNext-Next Generation Planning Vol. 6 (2018): Open call 5-24
Keywords: communicative interactions; facilitation; planning support systems; preliminary modelling; sketching; social systems